We See Data Everywhere Except in the Productivity Statistics. (28th September 2021) - Goodridge, Peter; Haskel, Jonathan; Edquist, Harald
Abstract : This paper uses Labor Force Survey data for European countries to estimate national investment in data assets, where the asset boundary is extended beyond that for software and databases as currently defined in the System of National Accounts. We find that: (a) in 2011–2018, 1.4 percent of EU‐28 employment was engaged in the formation of (software and) data assets, with a mean growth rate of 5 percent per annum; (b) on average in 2011–2016, expanding the asset boundary raises the level of own‐account GFCF in software and databases in the EU‐16 by 61 percent, and mean growth in real investment in own‐account software and data assets to 6.9 percent pa, compared to 2.7 percent pa in national accounts; (c) in 2011–2016, expansion of the asset boundary raises labor productivity growth in the EU‐13 from 0.79 percent to 0.83 percent pa, and the contribution of software and data capital deepening over three‐fold, from 0.03 percent to 0.10 percent pa.